Outbreak of Surgical Site Infections by Serratia marcescens Related to Degermation Brush. (March 2022) - Psaltikidis, E. Molina; Lima, T.; Fagnani, R.; Cardoso, L.; Bachur, L.F.; Höfling, C. Cruz; Mendes, E.; Oliveira, F.; Resende, M.; Velasco, N.; Moretti, M.L.
Abstract : Purpose: To describe the investigation and control of an outbreak of SSI caused by Serratia marcescens, identified from April/2020, mainly in neurosurgery and orthopedics Methods & Materials: Review of all surgical procedures and culture results with S. marcescens since January/2019. A case definition was proposed, hypotheses raised, microbiological review, and proposition of control measures. Results: The analysis of cultures confirmed the occurrence of an outbreak of SSI by S. marcescens . In total, 21 patients were identified, with surgeries occurring between March and June/2020 (8 neurosurgeries, 11 orthopedic, 1 cardiac, 1 vascular), being 7 meningitis, 1 osteomyelitis, 9 deep incisional infections, 4 superficial incisional.No related deaths. Clinical data and surgical records of the patients involved were evaluated, as well as materials and drugs used in the surgical field. No record of a common factor or non-conformity in the pre, intra and postoperative periods were observed. Proof of instrument sterilization was adequate. The hypothesis of contamination of antiseptics was considered, and 24 samples were collected for culture of all antiseptics available in the operating room and intensive care. All had negative results, except for 2 samples of brushes impregnated with degerming chlorhexidine, of the same brand and lot, with growth of S. marcescens . The product was immediately collected (June 22) from the entire hospital, blocking 8, 270 brushes out of a total of 15, 540 units from the batch put into use in February/2020. Further culture was carried out with 2 more samples from the same brush and batch in which there was, again, growth of S. marcescens, with the same phenotypic profile on the antibiogram as those isolated from the patients. Local and national health authorities were notified. Inoculation probably occurred in the degermation of the surgical site with brushes, which is common practice in these specialties. After removing the brushes, there were no new cases. Molecular analysis and chlorhexidine tolerance are scheduled. Conclusion: The SSI outbreak was caused by the contamination of brushes impregnated with degerming chlorhexidine with S. marcescens and the removal of the product was effective to control the outbreak.